The Amsterdam energy transition roadmap – introducing the City-zen methodology. Issue 3 (9th December 2019) - Dobbelsteen, Andy van den; Broersma, Siebe; Fremouw, Michiel; Blom, Tess; Sturkenboom, Jelle; Martin, Craig
Abstract : Purpose: City-zen is an EU-funded interdisciplinary project that aims to develop and demonstrate energy-efficient cities and to build methods and tools for cities, industries and citizens to achieve ambitious sustainability targets. As part of the project, an Urban Energy Transition Methodology is developed, elaborated and used to create Roadmaps, which indicate the interventions needed to get from the current situation to the desired sustainable future state of a city. For one of the partner cities, Amsterdam, such a Roadmap was developed. The paper aims to discuss these issues. Design/methodology/approach: This paper discusses the approach and methodology behind the City-zen Urban Energy Transition Methodology, with its six steps from the initial energy analysis to the roadmap towards a desired future state. The paper will illustrate this by results from the Amsterdam Roadmap study, in numbers and figures. Findings: The Roadmap study of Amsterdam revealed that the city can become energy neutral in its heat demand, but not in the production of sufficient electricity from renewables. Research limitations/implications: Although as yet only applied to the City of Amsterdam, the methodology behind the roadmap can be applied by cities across the world. Practical implications: An enormous effort is required in order to transform, renovate and adapt parts of the city. It was calculated, for instance, how many energy renovation projects, district heating pipes and photovoltaic panels will be annually needed in order to timely become carbon neutral, energy neutral and "fossil free". Social implications: The technical-spatial content of the Roadmap was presented to stakeholders of the Dutch capital city, such as politicians, energy companies, commercial enterprises, and not least citizens themselves. Although informed by scientific work, the Roadmap appealed too many, demonstrated by the extensive media coverage. Originality/value: The City-zen Methodology builds upon earlier urban energy approaches such as REAP (Tillie et al., 2009 ), LES (Dobbelsteen et al., 2011 ) and Energy Potential Mapping (Broersma et al., 2013), but creates a stepped approach that has not been presented and applied to a city as a whole yet. As far as the authors know, so far, an energy transition roadmap has never been developed for an entire city.